Role of dendrimers in advanced drug delivery and biomedical applications: a review - Akbarzadeh, A.; Khalilov, R.; Mostafavi, E.; Annabi, N.; Abasi, E.; Kafshdooz, T.; Herizchi, R.; Kavetskyy, T.; Saghf, S.; Nasibova, A.; Davaran, S. (Experimental Oncology, 2018)
Aim: Dendrimers dendritic structural design holds vast promises, predominantly for drug delivery, owing to their unique properties. Dendritic architecture is widespread topology found in nature and offers development of specific properties of chemical substances. Dendrimers are an ideal delivery vehicle candidate for open study of the effects of polymer size, charge, and composition on biologically relevant properties such as lipid bilayer interactions, cytotoxicity, bio-distribution, internalization, blood plasma retention time, and filtration. This article reviews role of dendrimers in advanced drug delivery and biomedical applications. Key Words: dendrimers, drug delivery vehicle, lipid bilayer interactions, dendritic architecture.